A compound coating agent for improving low-temperature germination rate and stress resistance of waxy corn seeds and a preparation method thereof

CN122936286APending Publication Date: 2026-10-20INNER MONGOLIA BAICHENG SEED IND CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611090990.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-22
Publication Date
2026-10-20

AI Technical Summary

Technical Problem

[0002]糯玉米早春播种普遍面临低温高湿的田间逆境,低温胁迫易破坏种子细胞膜结构、抑制生理代谢活性,造成种子萌发迟缓、发芽率下降、出苗整齐度差,严重影响糯玉米稳产生产

Benefits of technology

[0010]本发明的有益效果是:内层组分协同提升种子低温抗逆,改性氧化锌与柠檬酸钠保障包衣液稳定;外层温敏树脂智能控水,纳米粒缓释抑菌、减少烂种;双层膜致密不易脱落,显著提高糯玉米低温出苗率。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

This invention discloses a composite coating agent and its preparation method for improving the low-temperature germination rate and stress resistance of waxy corn seeds. The coating agent employs a dual-layer functional partition design: the inner layer contains betaine, spermidine, calcium chloride, and pectin-coated modified nano-zinc oxide, which stabilizes the embryo membrane structure and activates antioxidant enzymes at low temperatures, rapidly initiating embryo metabolism; the outer layer is a modified poly-N-isopropylacrylamide thermosensitive polymer with a minimum critical dissolution temperature of 8-12℃, loaded with ε-polylysine chitosan nanoparticles, which open pores at low temperatures to promote swelling and slow-release antibacterial activity, and partially shrinks upon heating to leave channels to balance water retention and air permeability. This invention also specifies the proportions of each component and the safe dosage of nano-zinc oxide, achieving industrial-scale production through a one-step layered coating process using a dual-nozzle fluidized bed. The synergistic effect of the inner and outer layers significantly improves the low-temperature germination rate and overall stress resistance of waxy corn seeds during the seedling stage.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of seed coating technology, specifically relating to a composite coating agent and its preparation method for improving the low-temperature germination rate and stress resistance of waxy corn seeds. Background Technology

[0002] Early spring sowing of waxy corn generally faces field stresses of low temperature and high humidity. Low temperature stress easily damages the seed cell membrane structure and inhibits physiological metabolic activity, resulting in delayed seed germination, decreased germination rate, and poor seedling uniformity, seriously affecting the stable yield of waxy corn. At the same time, low temperature and humid soil easily breed various soil-borne pathogens, inducing problems such as seed rot and seedling rot, further reducing the seedling survival rate. Currently, most conventional corn seed coating agents on the market are single-layer, single-function systems, which cannot simultaneously meet the needs of low-temperature germination promotion, antioxidant stress resistance, and long-term antibacterial effect. They have defects such as single function, poor component stability, and easy loss of active ingredients. Conventional coating systems lack intelligent temperature response capabilities and cannot dynamically adjust water and air permeability according to ambient temperature. Insufficient water absorption at low temperatures leads to germination inhibition, and water loss and stunted germination are prone to occur after the temperature rises. In addition, existing coating formulations are prone to problems such as metal ion hydrolysis and particle agglomeration and stratification in zinc-containing active systems, which seriously affect the stability and uniformity of the coating solution and restrict the application effect. Therefore, developing a two-layer composite coating agent with stable components, temperature-sensitive dynamic regulation capabilities, and the ability to significantly improve the low-temperature germination ability and seedling resistance of waxy corn seeds is of great application value for solving the problem of early spring low-temperature sowing, improving the field emergence quality of waxy corn, and enhancing the benefits of large-scale planting. Summary of the Invention

[0003] To address the aforementioned problems, this invention provides a composite coating agent and its preparation method for improving the low-temperature germination rate and stress resistance of waxy corn seeds. The product integrates temperature-sensitive water control, germination promotion and antibacterial properties, forms a stable film, and significantly enhances the low-temperature emergence and stress resistance of waxy corn.

[0004] To achieve the above objectives, the present invention adopts the following technical solution: A composite coating agent for improving the low-temperature germination rate and stress resistance of waxy corn seeds includes an inner functional metabolic coating and an outer temperature-sensitive, water-controlling, and antibacterial coating. The coating agent is prepared from the following raw materials in parts by weight: Based on 100 parts by weight of the total dry material of the inner coating, the inner coating raw materials are: 3-8 parts of betaine, 0.01-0.08 parts of spermidine, 2-5 parts of calcium chloride, 0.2-0.8 parts of modified nano zinc oxide, 0.3-0.6 parts of sodium citrate, and the remainder is the inner coating film-forming auxiliary material; Based on 100 parts by weight of the total dry material of the outer coating, the outer layer raw materials are: 15-25 parts of modified poly-N-isopropylacrylamide, 2-6 parts of ε-polylysine-coated chitosan nanoparticles, and the remainder is the outer layer film-forming auxiliary material. The modified poly(N-isopropylacrylamide) is a hydrophilic monomer copolymer modified product with a minimum critical dissolution temperature of 8-12℃; the composite coating increases the total dry weight of the waxy corn kernels by 3%-6% of the seed weight, the inner coating by 2%-4%, and the outer coating by 1%-2%.

[0005] Preferably, the inner film-forming auxiliary material and the outer film-forming auxiliary material are selected from one or more of polyvinyl alcohol and sodium carboxymethyl cellulose.

[0006] Preferably, the modified poly(N-isopropylacrylamide) thermosensitive polymer is a random copolymer of N-isopropylacrylamide and a hydrophilic monomer, wherein the hydrophilic monomer is selected from one or more of acrylamide, N-tert-butylacrylamide and N-hydroxymethylacrylamide.

[0007] Preferably, the sodium citrate, as a chelating stabilizer, can complex trace metal impurities in the coating system and inhibit the hydrolysis and aggregation of modified nano zinc oxide; the surface of the low-ester pectin-coated modified zinc oxide has an organic pectin layer, which improves the compatibility between inorganic powder and film-forming matrix, and the two work synergistically to improve the storage stability of the coating solution system.

[0008] Preferably, the preparation method of the composite coating agent for improving the low-temperature germination rate and stress resistance of waxy corn seeds includes the following specific preparation steps: S1. Dissolve betaine, spermidine, calcium chloride, and sodium citrate sequentially in deionized water and stir at 300-400 rpm for 20-30 minutes at room temperature until completely dissolved. Then add low-ester pectin-modified nano zinc oxide and disperse it at 3000-6000 rpm for 10-15 minutes using a high-shear emulsifier. Finally, add the inner layer film-forming excipients and stir evenly at 300-500 rpm to prepare a uniform and stable inner layer functional coating solution. S2. Add hydrophilic monomer copolymerized modified polyN-isopropylacrylamide to warm water at 25-30℃, stir at 350-450r / min for 20-30min until completely dissolved, then add ε-polylysine-coated chitosan nanoparticles, stir at 250-350r / min at low speed in the dark for 15-20min, and adjust the volume with the outer film-forming excipient to obtain a temperature-sensitive outer antibacterial coating solution; S3. Place the waxy corn seeds in a dual-nozzle fluidized bed coating machine, set the inlet air temperature to 30-35℃, the outlet air temperature to 25-30℃, and the fan frequency to 30-40Hz to maintain good fluidization of the seeds; first, turn on the first nozzle to spray the inner coating liquid obtained in S1 onto the seed surface, with an atomization pressure of 0.15-0.25MPa and a spraying rate of 8-12mL / min. After spraying, continue fluidization and drying for 2-3 minutes; after the inner surface is dry, turn on the second nozzle to spray the outer coating liquid obtained in S2 onto the seed surface that has been coated with the inner layer, with an atomization pressure of 0.15-0.25MPa and a spraying rate of 8-12mL / min. After spraying, continue fluidization and drying for 10-15 minutes to obtain double-coated waxy corn seeds.

[0009] Preferably, after the coating is completed, the seeds are dried at a low temperature with hot air at a temperature of 40-45℃ for 1.5-3 hours, and the final seed moisture content is controlled at 11%-13%, ensuring that the coating film structure is stable, does not crack or fall off, and is suitable for seed storage and low-temperature germination in the field.

[0010] The beneficial effects of this invention are: the inner layer components synergistically enhance the seed's resistance to low temperatures, and the modified zinc oxide and sodium citrate ensure the stability of the coating solution; the outer layer temperature-sensitive resin intelligently controls water, and the nanoparticles provide slow-release antibacterial properties and reduce seed rot; the double-layer film is dense and does not easily fall off, significantly improving the low-temperature emergence rate of waxy corn. Detailed Implementation

[0011] To make the objectives, technical solutions, and advantages of the embodiments of the present invention clearer, the technical solutions in the embodiments of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention. All other embodiments obtained by those skilled in the art based on the embodiments of the present invention without creative effort are within the scope of protection of the present invention.

[0012] Example 1: This Example 1 describes a composite coating agent for improving the low-temperature germination rate and stress resistance of waxy corn seeds. The coating agent is prepared from the following raw materials in parts by weight: Based on 100 parts by weight of the total dry material of the inner coating, the inner layer raw materials are: 5.5 parts betaine, 0.045 parts spermidine, 3.5 parts calcium chloride, 0.5 parts modified nano zinc oxide, and 0.45 parts sodium citrate. The remainder is the inner layer film-forming auxiliary material (polyvinyl alcohol and sodium carboxymethyl cellulose in a mass ratio of 3:1). Based on 100 parts by weight of the total dry weight of the outer coating material, the outer layer raw materials are: 20 parts of modified N-isopropylacrylamide, 4 parts of ε-polylysine-coated chitosan nanoparticles, and the remainder is the outer layer film-forming auxiliary material (polyvinyl alcohol and sodium carboxymethyl cellulose in a mass ratio of 3:1); the total weight gain of the coating is 4.5% of the seed weight (3% for the inner layer and 1.5% for the outer layer). The preparation method of modified nano zinc oxide is as follows: S1. Disperse nano zinc oxide in deionized water to prepare a 5% (w / w) suspension, and stir at 400 r / min for 30 min at room temperature; separately prepare a 2% (w / w) low-ester pectin aqueous solution. S2. Slowly add the pectin solution to the zinc oxide suspension while stirring at 600 r / min throughout the process. After the addition is complete, continue stirring at room temperature for 2 hours, let stand and age for 4 hours, filter, wash with water, and dry at low temperature to obtain low-ester pectin modified nano zinc oxide.

[0013] The preparation method of modified poly-N-isopropylacrylamide is as follows: S1. Weigh N-isopropylacrylamide and acrylamide, add them to a mixed solvent of anhydrous ethanol and deionized water in a volume ratio of 1:1, purge with high-purity nitrogen for 30 min to remove oxygen, and stir at room temperature at 300 r / min until the monomer is completely dissolved; then add the initiator azobisisobutyramidine hydrochloride, and continue to purge with nitrogen for 10 min. S2, polymerization was carried out at 65℃ and 400r / min under nitrogen protection for 6h; after cooling, it was dialyzed with pure water for 3d and freeze-dried to obtain modified poly-N-isopropylacrylamide. The measured minimum critical solution temperature (LCST) was 9.2℃.

[0014] The preparation method of ε-polylysine-coated chitosan nanoparticles is as follows: S1. Dissolve chitosan in 1% acetic acid aqueous solution to prepare a 0.3% chitosan solution, and stir at 450 r / min at room temperature until completely dissolved; prepare a 0.2 wt% sodium tripolyphosphate aqueous solution; S2. Add sodium tripolyphosphate solution dropwise to chitosan solution and stir magnetically at 700 r / min for 30 min to form chitosan nanoparticle dispersion; add ε-polylysine and stir at 300 r / min in the dark at room temperature for 2 h to obtain ε-polylysine coated chitosan nanoparticle suspension.

[0015] This embodiment describes a method for preparing a composite coating agent to improve the low-temperature germination rate and stress resistance of waxy corn seeds. The specific preparation steps are as follows: S1. Weigh betaine, spermidine, calcium chloride, and sodium citrate according to the formula, add them to deionized water, and stir at 350 r / min for 25 min at room temperature until completely dissolved; add pre-prepared low-ester pectin-modified nano zinc oxide, and disperse in a high-shear emulsifier at 4500 r / min for 12 min; then add polyvinyl alcohol and sodium carboxymethyl cellulose (mass ratio 3:1), and stir at 400 r / min to obtain the inner coating solution; S2. Add the modified poly(N-isopropylacrylamide) to 28°C warm water and stir at 400 rpm for 25 min until completely dissolved; add the pre-prepared ε-polylysine-coated chitosan nanoparticle suspension and stir at 300 rpm in the dark for 18 min; then add polyvinyl alcohol and sodium carboxymethyl cellulose (mass ratio 3:1) and stir until homogeneous to obtain the outer coating solution. S3. Load the glutinous corn seeds into a dual-nozzle fluidized bed with an inlet air temperature of 32℃, an outlet air temperature of 28℃, and a fan frequency of 35Hz. Spray the inner layer with the first nozzle at an atomization pressure of 0.20MPa and a spraying speed of 10mL / min, and then fluidize and dry for 2.5min. Then, switch to the second nozzle and spray the outer layer at the same pressure and speed, and then fluidize and dry for 12min. Finally, transfer the seeds to an oven at 42℃ for hot air drying for 2h, controlling the seed moisture content to 12%. This is the finished product.

[0016] Example 2: This Example 2 describes a composite coating agent for improving the low-temperature germination rate and stress resistance of waxy corn seeds. The coating agent is prepared from the following raw materials in parts by weight: Based on a total weight of 100 parts by weight of the inner coating dry material, the inner layer raw materials are: 3 parts betaine, 0.01 parts spermidine, 2 parts calcium chloride, 0.2 parts modified nano zinc oxide, and 0.3 parts sodium citrate. The remainder is the inner layer film-forming auxiliary material (polyvinyl alcohol and sodium carboxymethyl cellulose in a mass ratio of 3:1). Based on a total weight of 100 parts by weight of the outer coating dry material, the outer layer raw materials are: 15 parts of modified N-isopropylacrylamide, 2 parts of ε-polylysine-coated chitosan nanoparticles, and the remainder is the outer layer film-forming auxiliary material (polyvinyl alcohol and sodium carboxymethyl cellulose in a mass ratio of 3:1); the total weight gain of the coating is 3% of the seed weight (2% for the inner layer and 1% for the outer layer). The preparation methods of modified nano zinc oxide, modified poly-N-isopropylacrylamide, and ε-polylysine-coated chitosan nanoparticles in Example 2 are the same as those in Example 1; The preparation method of the composite coating agent for improving the low-temperature germination rate and stress resistance of waxy corn seeds in Example 2 is the same as that in Example 1.

[0017] Example 3: This Example 3 describes a composite coating agent for improving the low-temperature germination rate and stress resistance of waxy corn seeds. The coating agent is prepared from the following raw materials in parts by weight: Based on a total weight of 100 parts by weight of the inner coating dry material, the inner layer raw materials are: 8 parts betaine, 0.08 parts spermidine, 5 parts calcium chloride, 0.8 parts modified nano zinc oxide, and 0.6 parts sodium citrate. The remainder is the inner layer film-forming auxiliary material (polyvinyl alcohol and sodium carboxymethyl cellulose in a mass ratio of 3:1). Based on a total weight of 100 parts by weight of the outer coating dry material, the outer layer raw materials are: 25 parts of modified N-isopropylacrylamide, 6 parts of ε-polylysine-coated chitosan nanoparticles, and the remainder is the outer layer film-forming auxiliary material (polyvinyl alcohol and sodium carboxymethyl cellulose in a mass ratio of 3:1); the total weight gain of the coating is 6% of the seed weight (4% for the inner layer and 2% for the outer layer). The preparation methods of modified nano zinc oxide, modified poly-N-isopropylacrylamide, and ε-polylysine-coated chitosan nanoparticles in Example 3 are the same as those in Example 1; The preparation method of the composite coating agent for improving the low-temperature germination rate and stress resistance of waxy corn seeds in Example 3 is the same as that in Example 1.

[0018] Comparative Example 1: The coating agent of Comparative Example 1 was prepared from the following raw materials in parts by weight: Based on 100 parts by weight of the total dry material of the inner coating, the inner layer raw materials are: 5.5 parts betaine, 0.045 parts spermidine, 3.5 parts calcium chloride, 0.5 parts modified nano zinc oxide, and 0.45 parts sodium citrate. The remainder is the inner layer film-forming auxiliary material (polyvinyl alcohol and sodium carboxymethyl cellulose in a mass ratio of 3:1). Based on 100 parts by weight of the total dry weight of the outer coating material, the outer layer raw material consists of 4 parts of ε-polylysine-coated chitosan nanoparticles, with the remainder being the outer film-forming auxiliary material (polyvinyl alcohol and sodium carboxymethyl cellulose in a mass ratio of 3:1); the total weight gain of the coating is 4.5% of the seed weight (3% for the inner layer and 1.5% for the outer layer). The preparation methods of modified nano zinc oxide, modified poly-N-isopropylacrylamide and ε-polylysine-coated chitosan nanoparticles in Comparative Example 1 are the same as those in Example 1; The preparation method of the coating agent in Comparative Example 1 is the same as that in Example 1, except that 20 parts of modified poly(N-isopropylacrylamide) are replaced by polyvinyl alcohol and sodium carboxymethyl cellulose in a mass ratio of 3:1.

[0019] Comparative Example 2: The coating agent of Comparative Example 2 was prepared from the following parts by weight of raw materials: Based on 100 parts by weight of the total dry material of the inner coating, the inner layer raw materials are: 5.5 parts betaine, 0.045 parts spermidine, 3.5 parts calcium chloride, 0.5 parts nano zinc oxide, and 0.45 parts sodium citrate, with the remainder being inner layer film-forming auxiliary materials (polyvinyl alcohol and sodium carboxymethyl cellulose in a mass ratio of 3:1). Based on 100 parts by weight of the total dry weight of the outer coating material, the outer layer raw materials are: 20 parts of modified N-isopropylacrylamide, 4 parts of ε-polylysine-coated chitosan nanoparticles, and the remainder is the outer layer film-forming auxiliary material (polyvinyl alcohol and sodium carboxymethyl cellulose in a mass ratio of 3:1); the total weight gain of the coating is 4.5% of the seed weight (3% for the inner layer and 1.5% for the outer layer). The preparation method of modified poly-N-isopropylacrylamide and ε-polylysine-coated chitosan nanoparticles in Comparative Example 2 is the same as that in Example 1; The preparation method of the coating agent in Comparative Example 2 is the same as that in Example 1, except that the modified nano zinc oxide is replaced with unmodified ordinary nano zinc oxide.

[0020] Performance testing 1. Storage stability of coating solution Take 50 mL of fresh inner coating solution prepared in Examples 1-3 and Comparative Examples 1-2 respectively and place them in sealed transparent reagent bottles. Store them at room temperature for 7 days. Avoid shaking and direct sunlight during the test. After 7 days, visually observe the layering, precipitation and flocculation of each sample solution. Record whether there is precipitation, a small amount of precipitation or obvious layering phenomenon, so as to evaluate the storage stability of coating solutions with different formulations.

[0021] Table 1. Storage stability data of coating solutions for different samples

[0022] After standing for 7 days, the coating solutions in Examples 1-3 showed no stratification or flocculation, only trace precipitation, indicating good system stability that met production and storage requirements. Comparative Example 1, with an inner layer formulation consistent with the examples, exhibited good stability; however, Comparative Example 2, using unmodified nano-zinc oxide, showed powder agglomeration and sedimentation, resulting in significant stratification and flocculation, and markedly poorer stability. This demonstrates that low-ester pectin-modified nano-zinc oxide can effectively improve the dispersion uniformity and storage stability of the coating solution.

[0023] 2. Low-temperature germination test Select plump, uniform-sized, and undamaged waxy corn seeds. For each of Examples 1-3 and Comparative Examples 1-2, select 50 coated seeds. Place moist filter paper on a petri dish, arrange the seeds evenly, and incubate at 10℃ for 7 days. During the experiment, replenish water regularly to keep the filter paper moist. After 7 days, count the number of germinated seeds in each group and calculate the low-temperature germination rate.

[0024] Table 2. Test data of low-temperature germination test for different samples

[0025] Under 10℃ low-temperature conditions, the germination rate of waxy corn seeds in the example group was significantly higher than that in the two comparative groups, demonstrating excellent resistance to low-temperature germination. Comparative Example 1 lacked temperature-sensitive regulatory components, resulting in an unbalanced seed microenvironment and a low germination rate; Comparative Example 2 used unmodified zinc oxide, which had insufficient stress resistance and limited effect on promoting germination at low temperatures. This confirms that the compound formulation of the present invention can significantly improve the low-temperature germination performance of seeds.

[0026] 3. Field seed rot rate test Plump waxy corn seeds after coating were selected from each group. 100 seeds were sown in each group of Examples 1-3 and Comparative Examples 1-2. The seeds were sown in a low temperature and high humidity experimental field. After covering with soil, the soil in the field was kept continuously moist. After 20 days, all the seeds were dug up, the number of moldy and rotten seeds was counted, and the seed rot rate of each group was calculated.

[0027] Table 3. Field seed rot rate test data for different samples

[0028] Under low temperature and high humidity field conditions, the seed rot rate in the example group was significantly lower than that in the comparative group, demonstrating outstanding antibacterial and anti-mold effects. The outer ε-polylysine chitosan nanoparticles effectively inhibited soil pathogen infection, and combined with the dense double-layer coating structure, significantly reduced the probability of seed mold and rot. Comparative Example 1 lacked temperature-sensitive film-forming components, resulting in a loose film layer that was prone to mold growth under high humidity; Comparative Example 2 lacked modified zinc oxide for synergistic antibacterial effects and had poor anti-corrosion effects, verifying the synergistic anti-rot advantage of the components in this formulation.

[0029] 4. Coating film peeling rate Take 100g of coated waxy corn seeds from each group and place them in a standard experimental shaking tank. Shake at a constant speed of 200r / min for 10min at room temperature. Collect the detached powder and weigh it. The percentage of the mass of the detached powder to the total mass of the dry coating powder on the seed surface is taken as the coating film shedding rate.

[0030] Table 4. Data on the shedding rate of coating film for different samples

[0031] The coating film in the example group showed a low peeling rate, uniform and dense film formation, strong mechanical adhesion, and excellent abrasion resistance. The combination of film-forming excipients and modified nano-zinc oxide optimized the film structure, improving flexibility and density. Comparative Examples 1 and 2, lacking temperature-sensitive components or using unmodified zinc oxide, exhibited compromised film uniformity, decreased adhesion, and a significantly increased peeling rate, demonstrating that the formulation of this invention can effectively improve the adhesion of the coating film.

[0032] 5. Seed storage stability test Fifty coated seeds from each group were selected and stored in a sealed container at room temperature away from light for 30 days. Then, the germination rate was measured under the aforementioned low-temperature germination test conditions (10℃, constant temperature and humidity culture for 7 days). The changes in germination rate before and after storage were compared to evaluate the stability of seed storage.

[0033] Table 5. Data on the storage stability of different seed samples

[0034] After 30 days of storage at room temperature, the germination rate of seeds in the example group decreased only slightly, seed vigor remained stable, and storage performance was excellent. The double-layer composite coating effectively isolates moisture, oxygen, and pathogens, delaying seed aging. In contrast, the comparative example lacked sufficient protective barrier, making the seeds susceptible to moisture absorption, oxidation, and pathogen growth, resulting in severe vigor decline and a significant drop in germination rate. This demonstrates that the coating system of this invention can significantly improve seed storage stability.

Claims

1. A composite coating agent for improving the low-temperature germination rate and stress resistance of waxy corn seeds, comprising an inner functional metabolic coating and an outer temperature-sensitive water-controlling and antibacterial coating, characterized in that, The coating agent is prepared from the following raw materials in parts by weight: Based on 100 parts by weight of the total dry material of the inner coating, the inner coating raw materials are: 3-8 parts of betaine, 0.01-0.08 parts of spermidine, 2-5 parts of calcium chloride, 0.2-0.8 parts of modified nano zinc oxide, 0.3-0.6 parts of sodium citrate, and the remainder is the inner coating film-forming auxiliary material; Based on 100 parts by weight of the total dry material of the outer coating, the outer layer raw materials are: 15-25 parts of modified poly-N-isopropylacrylamide, 2-6 parts of ε-polylysine-coated chitosan nanoparticles, and the remainder is the outer layer film-forming auxiliary material. The modified poly(N-isopropylacrylamide) is a hydrophilic monomer copolymer modified product with a minimum critical dissolution temperature of 8-12℃; the composite coating increases the total dry weight of the waxy corn kernels by 3%-6% of the seed weight, the inner coating by 2%-4%, and the outer coating by 1%-2%.

2. The composite coating agent for improving the low-temperature germination rate and stress resistance of waxy corn seeds according to claim 1, characterized in that, The inner film-forming material and the outer film-forming material are selected from one or more of polyvinyl alcohol and sodium carboxymethyl cellulose.

3. The composite coating agent for improving the low-temperature germination rate and stress resistance of waxy corn seeds according to claim 1, characterized in that, The modified poly(N-isopropylacrylamide) thermosensitive polymer is a random copolymer of N-isopropylacrylamide and a hydrophilic monomer, wherein the hydrophilic monomer is selected from one or more of acrylamide, N-tert-butylacrylamide and N-hydroxymethylacrylamide.

4. The composite coating agent for improving the low-temperature germination rate and stress resistance of waxy corn seeds according to claim 1, characterized in that, The modified nano zinc oxide is a low-ester pectin-coated modified nano zinc oxide; the sodium citrate is a chelating stabilizer for the inner coating.

5. A method for preparing a composite coating agent for improving the low-temperature germination rate and stress resistance of waxy corn seeds according to any one of claims 1-4, characterized in that, The specific preparation steps are as follows: S1. Dissolve betaine, spermidine, calcium chloride, and sodium citrate sequentially in deionized water and stir at 300-400 rpm for 20-30 minutes at room temperature until completely dissolved. Then add low-ester pectin-modified nano zinc oxide and disperse it at 3000-6000 rpm for 10-15 minutes using a high-shear emulsifier. Finally, add the inner layer film-forming excipients and stir evenly at 300-500 rpm to prepare a uniform and stable inner layer functional coating solution. S2. Add hydrophilic monomer copolymerized modified polyN-isopropylacrylamide to warm water at 25-30℃, stir at 350-450r / min for 20-30min until completely dissolved, then add ε-polylysine-coated chitosan nanoparticles, stir at 250-350r / min at low speed in the dark for 15-20min, and adjust the volume with the outer film-forming excipient to obtain a temperature-sensitive outer antibacterial coating solution; S3. Place the waxy corn seeds in a dual-nozzle fluidized bed coating machine, set the inlet air temperature to 30-35℃, the outlet air temperature to 25-30℃, and the fan frequency to 30-40Hz to maintain good fluidization of the seeds; first, turn on the first nozzle to spray the inner coating liquid obtained in S1 onto the seed surface, with an atomization pressure of 0.15-0.25MPa and a spraying rate of 8-12mL / min. After spraying, continue fluidization and drying for 2-3 minutes; after the inner surface is dry, turn on the second nozzle to spray the outer coating liquid obtained in S2 onto the seed surface that has been coated with the inner layer, with an atomization pressure of 0.15-0.25MPa and a spraying rate of 8-12mL / min. After spraying, continue fluidization and drying for 10-15 minutes to obtain double-coated waxy corn seeds.

6. The method for preparing a composite coating agent for improving the low-temperature germination rate and stress resistance of waxy corn seeds according to claim 5, characterized in that, After coating, the seeds are dried at a low temperature with hot air at 40-45℃ for 1.5-3 hours. The final seed moisture content is controlled at 11%-13%, ensuring that the coating film structure is stable, does not crack, and does not fall off, making it suitable for seed storage and low-temperature germination in the field.